Mining the bacterial genome to discover new antimicrobial molecules - Wenjie Liang; Julien Diana (EMBO Molecular Medicine)
Abstract Multidrug resistance is one of the major public health issues the world is facing today. However, the World Health Organization (WHO) revealed recently that there has been little progress in the development of new antibiotics to tackle drug‐resistant infections. By mining the bacterial genome database, Zhu et al, in the last issue of EMBO Molecular Medicine, report a defensin expressed by human oral actinomyces, actinomycesin, and characterize its anti‐infectious capacity (Zhu et al, 2021). They demonstrate the safety and efficacy of this bacterial antimicrobial peptide (AMP) against various bacterial strains, describe its mode of action, and validate its use as systemic drug therapy against bacterial infections in mice. This study highlights human oral bacteria as a source of antimicrobial agents that need to be considered in the future to fight multidrug‐resistant bacteria.